2001
DOI: 10.1046/j.1525-139x.2001.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

How Important Is Atheromatous Renal Artery Stenosis as a Cause of End‐Stage Renal Disease?

Abstract: In recent years atheromatous renal artery stenosis has been proposed as a common and potentially preventable cause of end-stage renal disease (ESRD). Occlusive renal artery disease causes renal failure that can be reversed following successful revascularization, but this scenario is relatively rare. Nonocclusive renal artery stenosis is commonly found in association with varying degrees of renal impairment. However, recent evidence and clinical observation suggest that a cause and effect relationship is unlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…When endovascular or surgical repair is achieved early after loss of renal perfusion or in kidneys for which some collateral blood flow has been preserved (38), salvage of renal function sometimes can be accomplished. However, most patients have little return of GFR, and some lose function further, leading some authors to argue that renal revascularization has little meaningful benefit (39). Our results suggest that part of the underlying renal injury represents a transition to inflammatory and fibrotic injury that does not resolve with restoring renal blood flow alone.…”
Section: Discussionmentioning
confidence: 75%
“…When endovascular or surgical repair is achieved early after loss of renal perfusion or in kidneys for which some collateral blood flow has been preserved (38), salvage of renal function sometimes can be accomplished. However, most patients have little return of GFR, and some lose function further, leading some authors to argue that renal revascularization has little meaningful benefit (39). Our results suggest that part of the underlying renal injury represents a transition to inflammatory and fibrotic injury that does not resolve with restoring renal blood flow alone.…”
Section: Discussionmentioning
confidence: 75%
“…This assumption is based on the consideration that apart from luminal narrowing of the renal artery, a combination of arteriolar and atheroembolic damage (i.e., cholesterol microembolism) is thought to contribute to progressive loss of renal function. Actually, smoking is a known risk factor for cholesterol microembolism (64).…”
Section: Smoking and Atherosclerotic Renal Artery Stenosis/ischemic Nmentioning
confidence: 99%
“…On the one hand, the advocates of an aggressive approach [31,32] underline the likely prospect of recovering renal function in many patients and the chance of preventing a likely progression towards chronic renal failure. On the other, the supporters of the wait-and-see approach [33][34][35] raise the objection that no randomised trial has ever demonstrated the superiority of revascularization over medical treatment in regard to blood pressure control and renal function recovery. They also stress the fact that the revascularization manoeuvres are weighed down by frequent complications.…”
Section: The Controversy Surrounding Revascu-larizationmentioning
confidence: 99%